Changing epidemiology of bloodstream infections associated with central venous catheters in patients after stem cell transplantation: increasing frequency of identification of Gram-negative pathogens - Raddaoui, Anis; Mezzi, Khaoula; Belloumi, Dorra; Frigui, Siwar; Ben Othmen, Tarek; Abdejlil, Nour; Chebbi, Yosra; Achour, Wafa (Journal of Medical Science, 2026)
Introduction. The frequent use of central venous catheters (CVC) in haematopoietic stem cell (HSC) transplant patients exposes them to a high risk of catheter-related bloodstream infections (CRBSI). The aim of this study was to estimate the prevalence of CRBSI in HSC transplant patients and to describe their clinical and bacteriological characteristics. Material and methods. A retrospective study (January 2011-December 2022) including 60 episodes of CRBSI occurring in the pre- or post-HSC transplant period in 56 patients was conducted in the Haematology and Transplant Department of the National Bone Marrow Transplant Centre. Results. The prevalence of CRBSI was 4.9%. The median time between CVC placement and CRBSI was nine days. Gram-negative bacilli (GNB) CRBSI (N=33, 55%) were more frequent than gram-positive cocci (GPC) CRBSI (N=27, 45), with a GNB/GPC ratio of less than one before 2019, rising to two between 2019 and 2022. First-line antibiotic therapy was based mainly on Piperacillin-tazobactam (60%). Removal of the CVC was indicated in 51% of cases. Mortality associated with CRBSI was 0.32% (4/1217). Conclusion. The increase in CRBSI prevalence and the high rate of antibiotic resistance highlight the need for heightened awareness, ongoing training for healthcare staff, and judicious antibiotic use.